Altered Expression of Type-1 and Type-2 Cannabinoid Receptors in Celiac Disease - Battista, Natalia; Di Sabatino, Antonio; Di Tommaso, Monia; Biancheri, Paolo; Rapino, Cinzia; Giuffrida, Paolo; Papadia, Cinzia; Montana, Chiara; Pasini, Alessandra; Vanoli, Alessandro; Lanzarotto, Francesco; Villanacci, Vincenzo; et al. (PloS one, 2013)
Anandamide (AEA) is the prominent member of the endocannabinoid family and its biological action is mediated through the binding to both type-1 (CB1) and type-2 (CB2) cannabinoid receptors (CBR). The presence of AEA and CBR in the gastrointestinal tract highlighted their pathophysiological role in several gut diseases, including celiac disease. Here, we aimed to investigate the expression of CBR at transcriptional and translational levels in the duodenal mucosa of untreated celiac patients, celiac patients on a gluten-free diet for at least 12 months and control subjects. Also biopsies from treated celiac patients cultured ex vivo with peptic-tryptic digest of gliadin were investigated. Our data show higher levels of both CB1 and CB2 receptors during active disease and normal CBR levels in treated celiac patients. In conclusion, we demonstrate an up-regulation of CB1 and CB2 mRNA and protein expression, that points to the therapeutic potential of targeting CBR in patients with celiac disease.